Threshing rig (Goodhue County Historical Society, 1166 Oak Street, Red Wing, Minnesota 55066; http://www.goodhuehistory.mus.mn.us)
Near Lester Swanson farm
United States
Minnesota
Goodhue
Cannon Falls Township
Near Lester Swanson farm
Keywords: Cannon Falls Township; Steam engines; Trees; Agriculture